Direct and indirect associations of experience of racial discrimination, dietary patterns and obesity in adults from southern Brazil - Marcos Fanton; Ylana Elias Rodrigues; Ilaine Schuch; Caroline Marques de Lima Cunha; Marcos Pascoal Pattussi; Raquel Canuto (Cambridge University Press, 2024)
Abstract Objective: To analyse the direct and indirect associations of experience of racial discrimination on dietary patterns (DP), obesity and abdominal obesity. Design: This is a cross-sectional population-based study. The main exposure was self-reported experiences of racial discrimination (Experiences of Discrimination scale). The mediator variables were the DP: healthy, Brazilian traditional, sugar and carbohydrates, and fast food. The outcomes were obesity (BMI ≥ 30 kg/m2) and abdominal obesity (waist circumference ≥ 88 cm for women; ≥ 102 cm for men). Structural equation modelling was applied. Setting: Porto Alegre, Brazil. Participants: Totally, 400 adults aged between 20 and 70 years were participated. Results: The mean age of participants was 47·2 years (s d = 13·9), and 75 % were women. Experiencing racial discrimination had a positive direct effect on obesity (healthy DP: β = 0·153, P < 0·05; Brazilian DP: β = 0·156, P < 0·05; sugar and carbohydrates DP: β = 0·156, P < 0·05; and fast-food DP: β = 0·153, P < 0·05) and abdominal obesity (healthy DP: β = 0·206, P < 0·01; Brazilian DP: β = 0·210, P < 0·01; sugar and carbohydrates DP: β = 0·204, P < 0·01; and fast-food DP: β = 0·204, P < 0·01). The experience of racial discrimination did not have a direct effect on DP, nor did it exert an indirect effect on obesity and abdominal obesity through any DP. Conclusions: A higher experience of racial discrimination is associated with obesity and abdominal obesity, independent of diet.